2020
DOI: 10.1038/s42003-020-1024-z
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila melanogaster behaviour changes in different social environments based on group size and density

Abstract: Many organisms, when alone, behave differently from when they are among a crowd. Drosophila similarly display social behaviour and collective behaviour dynamics within groups not seen in individuals. In flies, these emergent behaviours may be in response to the global size of the group or local nearest-neighbour density. Here we investigate i) which aspect of social life flies respond to: group size, density, or both and ii) whether behavioural changes within the group are dependent on olfactory support cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 42 publications
0
51
0
Order By: Relevance
“…Similar factors appear to influence the rhythms of flies. Although, flies are not classified as social, they form groups, interact with each other, adjusting their interactive behavior to group size (Rooke et al, 2020) and their clocks can be entrained by pheromones (Levine et al, 2002;Krupp et al, 2008) and vibrations (Simoni et al, 2014). Clearly, in flies, social synchronization has not the same significance as it has in bees, but studying it might help to unravel the underlying mechanisms.…”
Section: The Relevance Of Zeitgebers Differs Between Flies and Beesmentioning
confidence: 99%
“…Similar factors appear to influence the rhythms of flies. Although, flies are not classified as social, they form groups, interact with each other, adjusting their interactive behavior to group size (Rooke et al, 2020) and their clocks can be entrained by pheromones (Levine et al, 2002;Krupp et al, 2008) and vibrations (Simoni et al, 2014). Clearly, in flies, social synchronization has not the same significance as it has in bees, but studying it might help to unravel the underlying mechanisms.…”
Section: The Relevance Of Zeitgebers Differs Between Flies and Beesmentioning
confidence: 99%
“…The opposite prediction is also possible, namely high assortativity in low density due to the potential for more structured populations, although if this persists throughout the reproductive stage, this could incur an opportunity cost for individuals in low density populations (e.g., low mating encounter rate). Recent studies have shown that groups of adult Drosophila tend to display some level of aggregation and social interactions that are density-dependent, with social distancing determined by specific neuronal circuits activated by contact amongst individuals in the groups and cluster formation dependent upon olfactory cues (Jiang et al 2020;Rooke et al 2020). These evidences suggest that density-dependent effects can modulate how individuals respond to social cues, ultimately affecting the propensity of individuals to form (dis)similar clusters within the social network structure.…”
Section: Density-dependent Effects On Host-microbe Interactions and Tmentioning
confidence: 99%
“…Drosophila melanogaster larvae form simple cooperative group aggregates while feeding, which has been hypothesized to increase their fitness by providing defense against predation, as well as enabling individuals to communally digest food substrates more easily (Prokopy & Roitberg, 2001;Sokolowski, 2010;Wu et al, 2003). Previous studies have suggested that in Drosophila and several other insect species, the formation and maintenance of larval aggregation is primarily regulated by the chemosensory detection of aggregation pheromones, as well as other sensory modalities (Leonhardt et al, 2016;Louis & de Polavieja, 2017;Rooke et al, 2020;Steiger & Stokl, 2017;Symonds & Wertheim, 2005;Thibert et al, 2016). Specifically, in Drosophila melanogaster, at least two pheromones produced by larvae have been shown to act as chemoattractants (Mast et al, 2014).…”
Section: Introductionmentioning
confidence: 99%